Sportivnaja nauka i sportivnaja pedagogika v XXI veke - Tajmazov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The article concerns significance of the sport, as well as the position of sports science in the modern Russian soci-ety. Progressive trends of its development are laid down. Special attention is paid to credit module system of the higher education has been introducing in the sports higher schools. The main purpose of it is to rise the quality of the students' education. The problem of the deviant behavior now spreading among young people, has been viewed; and the ways of resistance to this tendency by the facilities of the physical culture and sport are indicated.